THE EFFECTS OF DIFFERENT CONCENTRATIONS OF ROSEMARY (ROSMARINUS OFFICINALIS) EXTRACT ON THE SHELF LIFE OF HOT-SMOKED AND VACUUM-PACKED LUCIOBARBUS ESOCINUS FILLETS - Coban, Ozlem Emir; Ozpolat, Emine (Wiley, 2013)
In this study, the effects of the different concentrations of rosemary (Rosmarinus officinalis) extract on the shelf life of hot-smoked and vacuum-packed Luciobarbus esocinus fillets were investigated in terms of its microbiological, chemical and sensory quality. The results showed that rosemary extract had a significant effect on lactic acid bacteria, psychrophile bacteria, yeast-mold, thiobarbituric acid and peroxide value during storage (P<0.05). The shelf lives of smoked L.esocinus fillets to which rosemary extract was added were determined to be 42 days for 400mL/L, 84 days for 600mL/L and 800mL/L brine. Also, that in the control group (without rosemary extract) was determined to be 42 days. Rosemary extract was effective in controlling the growth of bacteria and chemical indices. PRACTICAL APPLICATIONS Hot smoked fish stored in anaerobic conditions is very sensitive to deterioration and, based on sensory evaluation, has a limited shelf life ranging from 3 to 4 weeks at refrigerator temperature. Natural extracts have proven to be an effective preservation method for the extension of shelf life of foods. Our study has clearly shown that addition of rosemary extract in smoked fish resulted in longer shelf life, and this method could be commercially used.
Keywords: Quality; Smoking; Storage; Stability; Food